2020
DOI: 10.1111/jocs.14537
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐arterial and total‐arterial coronary revascularization: Past, present, and future perspective

Abstract: Background and Aim of the Study: Although abundant biological, clinical, and scientific evidence exists on the superiority of multi-arterial (MAR) and total-arterial revascularization (TAR) over the conventional strategy with a single internal thoracic artery, only 10% of patients undergoing coronary artery bypass grafting (CABG) in the United States receives a second arterial conduit, and only 5% of patients receives TAR. Methods and Results: In January 2020, the authors performed comprehensive search to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 87 publications
(137 reference statements)
0
11
0
1
Order By: Relevance
“…After demonstrating the safety and reproducibility of this approach in a case series, and through significant technological improvements of the following generations of the da Vinci robotic system, multiple conduit harvesting for more complex, off-pump grafting strategies became possible. [ 53 55 ] It has been extensively demonstrated that robotic-assisted, endoscopic, multivessel CABG procedures are safe, feasible and reproducible and lead to excellent outcomes. [ 6 , 8 , 56 , 57 ]…”
Section: Techniques Of Minimally Invasive Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…After demonstrating the safety and reproducibility of this approach in a case series, and through significant technological improvements of the following generations of the da Vinci robotic system, multiple conduit harvesting for more complex, off-pump grafting strategies became possible. [ 53 55 ] It has been extensively demonstrated that robotic-assisted, endoscopic, multivessel CABG procedures are safe, feasible and reproducible and lead to excellent outcomes. [ 6 , 8 , 56 , 57 ]…”
Section: Techniques Of Minimally Invasive Coronary Artery Bypass Graftingmentioning
confidence: 99%
“…Total arterial grafting is more beneficial in both short and long-term outcomes and its use should be encouraged. 4 , 5 , 24 , 26 This technique minimizes the risk of stroke and has better patency. Drawbacks of this approach include DSWI and longer procedural time, as total arterial grafting is a more challenging surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“… 33 , 34 Later on, significant technological improvements in the da Vinci robotic system enabled surgeons to perform off-pump multiarterial TE-CABG. 35 The value of TE-CABG versus RA-CABG is not limited to the presence or absence of an incision required to perform the surgery but rather to the possibility of expanding the procedure to multivessel grafting by facilitating RITA harvest and performing multiple anastomoses. 36 …”
Section: Robotic Midcabmentioning
confidence: 99%